Comparison of Damage to Wood Pallets in Use with Damages Occurring Using the Virginia Tech FasTrack Simulation of Pallet Use - Jorge A. Masis Ulloa; Laszlo Horvath; Marshall S. White (BioResources, 2023)
The durability of a pallet affects the amount of use a pallet can withstand before functionality is lost. A reliable prediction of durability can be used to determine the effect of pallet performance on supply chain operating costs. The objective of this research was to correlate damage modes, location, severity, and frequency observed for pallet in the field, to damages observed during Virginia Tech’s FasTrack simulation system. Several 1219 mm x 1016 mm (48 x 40 inch) stringer class wooden pallets used in the field were inspected for damages, and the results were compared to historical pallet damage information from FasTrack. The pallet damage behavior did not change for different levels of damage severity, which indicates that pallets fail as the initial damage worsens due to prolonged use. Inspected pallets from the field showed high damage occurrence on the stringer notches and bottom lead deckboards. Pallets tested via FasTrack exhibited significantly more top deck and end board damage and less stringer damage than observed in the field.